DENIAL OF TRANSLATION AND DESIRE TO TRANSLATE - Gambier, Yves (Vertimo studijos, 2017)
Translating and translation are transformed with Information and Communication Technology (ICT). Yesterday, translation was invisible, denied – as a need, as an activity, as a profession, and as a discipline. Within three decades, a new work environment is shaking up the translators’ world. New types of translators are emerging. The balance between supply and demand is changing. However, we still need adequate tools and methods to investigate the new hierarchy which has become established between translators, between different kinds of job markets.